WORK DISCIPLINE, WORK ENVIRONMENT, AND COMMUNICATION AS DETERMINANTS OF EMPLOYEE JOB SATISFACTION: EVIDENCE FROM PT BPR SANTI PALA - Widiantara, I Putu Pande Dimas; Saraswati, Ni Putu Ayu Sintya; Utami, Ni Made Satya (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
Human resources are the most valuable and important assets of a company, because the success of an organization is determined by its human elements. The purpose of this study is to determine the impact of work discipline, work environment, and communication on employee job satisfaction. The research was conducted at PT. BPR Santi Pala, located on Jl. Raya Darmasaba, Abiansemal Badung, Bali. The population consisted of all employees of PT BPR Santi Pala, and the sample consisted of 31 employees. The sampling technique used was saturated sampling, which used the entire population as the sample. The data was then analyzed using reliability, validity, multicollinearity, normality, multiple linear regression analysis, heteroscedasticity, determination analysis (R2), multiple correlation analysis (R), F test, and t test. Based on the findings of the study, it was stated that work discipline significantly and positively affects employee job satisfaction, the work environment significantly and positively affects employee job satisfaction, and communication significantly and positively affects employee job satisfaction.